2010
DOI: 10.1002/mabi.201000231
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Blue‐Conjugated Hydrogel Nanoparticles and Tumor‐Cell Targeted Photodynamic Therapy

Abstract: Methylene blue-conjugated polyacrylamide nanoparticles are prepared through a microemulsion polymerization, after conjugation of the dye with a monomer. The nanoparticles have a 50-60 nm diameter in solution. This conjugation method enables a large increase in loading of methylene blue per nanoparticle and also minimizes dye leaching out of the nanoparticle. Furthermore, the dye content can be controlled by variation of the dye amount, enabling a more refined control of the singlet oxygen production ability. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 37 publications
2
115
0
Order By: Relevance
“…Data showed that the PDT induced cell death increased with NP dose and irradiation time [150]. Improvement of target cell specificity was also noticed in 5,10,15,20-tetraphenylporphyrin loaded into polymeric micelles modified with tumor specific monoclonal antibody 2C5 (mAb 2C5) against murine Lewis lung carcinoma.…”
Section: Actively Targeted Liposomesmentioning
confidence: 93%
“…Data showed that the PDT induced cell death increased with NP dose and irradiation time [150]. Improvement of target cell specificity was also noticed in 5,10,15,20-tetraphenylporphyrin loaded into polymeric micelles modified with tumor specific monoclonal antibody 2C5 (mAb 2C5) against murine Lewis lung carcinoma.…”
Section: Actively Targeted Liposomesmentioning
confidence: 93%
“…Many other studies evidenced this potential such as cisplatin loaded hydrogel NPs for ovarian cancer therapy [91], hydrogel NPs for tumor-cell targeted photodynamic therapy [92].…”
Section: F3 Peptide Conjugated Nps Targeting Nclmentioning
confidence: 99%
“…Hence the localization of PS is crucial for the targeted as well as efficient PDT. Hydrogels are considered to be the ideal platforms for PS delivery, and the recent progresses of hydrogels used for PDT are summarized in Table 1 [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Hydrogels For Photodynamic Therapymentioning
confidence: 99%
“…Besides, other PSs such as methylene blue (MB) and 2-devinyl-2-(1-hexyloxyethyl) pyropheophorbide (HPPH) conjugated to PAA nanogels through covalent bonds have also been reported by Kopelman's group [24][25][26]. For example, amine-functionalized biodegradable PAA nanogels were synthesized for cancer theranostics, including active Poloxamer 407 5-ALA Thermosetting gel Thermosetting gel for PS precursor delivery [32] PEGDA, PEG, PTA ZnPc Photopolymerisable hydrogel In situ gelation through photopolymerization for localized PDT [33] TiO2 and PEGDA TiO2 Photopolymerisable hydrogel Inorganic/organic hybrid hydrogel system [34] PVA and sodium tetraborate MB Macrogels PS-loading hydrogel for drug-resistant bacterial killing [35] HEMA and MAA TMPyP Macrogels Localizing the photocytotoxic effect of PSs at a biomaterial surface for PACT [36] PMVE and MA MB Macrogels Electrically-responsive anti-adherent hydrogels for PACT [37] HPMC and chitosan TBO Macrogels PS-loaded hydrogels for the treatment of biofilm [38] PAA MB derivatives Macrogels PS-loaded hydrogel was found to be active for four-cycle PACT [39] Figure 1 Synthetic route of the multifunctional polymeric nanomedicine.…”
Section: Hydrogels For Photodynamic Therapymentioning
confidence: 99%